A recombinant O-polysaccharide-protein conjugate approach to develop highly specific monoclonal antibodies to Shiga toxin-producing Escherichia coli O157 and O145 serogroups - Castillo, Daniela S. (PLoS One, 2017)
Shiga toxin-producing Escherichia coli (STEC) is the major etiologic agent of hemolytic-uremic syndrome (HUS). The high rate of HUS emphasizes the urgency for the implementation of primary prevention strategies to reduce its public health impact. Argentina shows the highest rate of HUS worldwide, being E. coli O157 the predominant STEC-associated HUS serogroup (>70%), followed by E. coli O145 (>9%). To specifically detect these serogroups we aimed at developing highly specific monoclonal antibodies (mAbs) against the O-polysaccharide (O-PS) section of the lipopolysaccharide (LPS) of the dominant STEC-associated HUS serogroups in Argentina. The development of hybridomas secreting mAbs against O157 or O145 was carried out through a combined immunization strategy, involving adjuvated-bacterial immunizations followed by immunizations with recombinant O-PS-protein conjugates. We selected hybridoma clones that specifically recognized the engineered O-PS-protein conjugates of O157 or O145 serogroups. Indirect ELISA of heat-killed bacteria showed specific binding to O157 or O145 serogroups, respectively, while no cross-reactivity with other epidemiological important STEC strains, Brucella abortus, Salmonella group N or Yersinia enterocolitica O9 was observed. Western blot analysis showed specific recognition of the sought O-PS section of the LPS by all mAbs. Finally, the ability of the developed mAbs to bind the surface of whole bacteria cells was confirmed by flow cytometry, confocal microscopy and agglutination assays, indicating that these mAbs present an exceptional degree of specificity and relative affinity in the detection and identification of E. coli O157 and O145 serogroups. These mAbs may be of significant value for clinical diagnosis and food quality control applications. Thus, engineered O-PS specific moieties contained in the recombinant glycoconjugates used for combined immunization and hybridoma selection are an invaluable resource for the development of highly specific mAbs.